SYNTHESIS AND PHARMACOLOGICAL EVALUATION: ANTIMICROBIAL, ANTI-INFLAMMATORY, ANALGESIC, ULCEROGENIC PROPERTIES OF SEVERAL BIS-HETEROCYCLIC DERIVATIVES - Ravindra Kumar; Hament Panwar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
In Medicinal chemistry, heterocyclic derivatives contributed the largest classical division of organic chemistry. Thiadiazole compounds have been know many biological activities such as hypoglycemic, anticancer, anti-inflammatory, anti-asthmatic, antihypertensive and etc. On this research, several 1,1-Bis [2-2-(5-(arylidene)imino-1,3,4-thiadiazol-2-yl) methyl amino- 1,3,4-thiadiazo-5-yl] cyclopropane 5(a-h) have been synthesized from cyclopropane dicarboxylic acid comprising thiadiazole moieties. All the synthesized compounds have been characterized by elemental (C,H,N) and spectral (I.R., 1H- NMR, Mass) analysis. Furthermore, all synthesized compounds were screened for their antifungal, antimicrobial, anti-inflammatory, analgesic, ulcerogenic and toxic activities. The Compound 5f, 3-chlorophenyl substituted was found the most potent in antimicrobial spectrum against all the used microbes. On the other hand, compound 5g, 4-hydroxy-3-methoxy phenyl substituted was found the most potent in anti-inflammatory, analgesic, and ulcerogenic activities which further evaluated for lesser toxicity test.Key words: Bis-phenylarylidinylthiadiazolidinone cyclopropane, anti-microbial, anti-inflammatory, analgesic, ulcerogenic and toxicity studies